Secret cables of the Comintern, 1933-1943 - Firsov, Fridrich Igorevič 1931- (Annals of communism, 2014)
"Drawing on secret and therefore candid coded telegraphs exchanged between Communist Party leaders around the world and their overseers at the Communist International (Comintern) headquarters in Moscow, this book uncovers key aspects of the history of the Comintern and its significant role in the Stalinist ruling system during the years 1933 to 1943. New information on aspects of the People's Front in France, civil wars in Spain and China, World War II, and the extent of the Comintern's cooperation with Soviet intelligence is brought to light through these archival records, never examined before"--